Quality changes in fresh-cut ‘Rocha’ pear as affected by oxygen levels in modified atmosphere packaging and the pH of antibrowning additive - Gomes, M. Helena (2013)
Respiratory behavior of fresh-cut ‘Rocha’ pear suggests that optimization of O2 concentration inside modified atmosphere packages (MAP) is of limited benefit. To test this hypothesis, packages were designed to achieve three equilibrium O2 partial pressures. Fresh-cut ‘Rocha’ pear was treated with 250 mM calcium ascorbate solutions buffered at pH 3.0 and pH 7.0, packaged under the three MAP conditions, and stored at 5 ◦C for 20 d. Actual O2 levels (mean ± confidence interval at 95%) during the experiment were 16.7 ± 0.2, 1.8 ± 0.2 and 0.25 ± 0.04 kPa with corresponding CO2 levels of 1.3 ± 0.1, 4.3 ± 0.2 and 6.5 ± 0.4 kPa. Changes in quality attributes related to fruit metabolism, namely firmness, titratable acidity, pH, and soluble solids content were not affected by O2 levels. Overall changes in water activity, levels of ascorbate, and microbial growth were also independent of O2 levels. Oxygen partial pressure inside the packages affected browning, which was more intense at 16.7 kPa O2. Sensory analyses performed after 8 d in storage confirmed that panelists perceived the differences in color but did not detect differences in firmness or taste among the samples under different O2 levels. Browning was more intense at pH 3.0 than at pH 7.0 but the kinetics of other quality attributes were not affected by pH. No significant improvements of quality attributes dependent on the physiology of respiration of fresh-cut ‘Rocha’ pear can be obtained by reducing O2 partial pressure inside the packages.